An overview of the Northern Ireland Education Outcomes Linkage (EOL) (2018/2019) database - McCarter, Rachel; IJpelaar, Jos; Murphy, Jamie; McDowell, Ronald (International Journal of Population Data Science, 2025)
Objectives The Education Outcomes Linkage (EOL) is a database of post-primary schools’ data for pupils aged 14 and over in Northern Ireland (NI). This study provides a broad description of this new dataset at its first wave (2018/2019). Methods Wave one of EOL includes the 2018/2019 NI Exams database linked to the 2018 School Census data to create a spine of pupils aged 14 and over who undertook at least one exam in 2018/2019. School census/attendance data for the previous three years, exams taken by this cohort prior to 2018/2019 and the 2018/2019 School Leavers Study were also linked. Conventional descriptive statistics were used to summarise the cohort and perform some initial comparisons between groups of interest. Results The population comprised 52,806 pupils aged 14-18 years (mean:15.6; SD:1.0%) in July 2018 across 191 schools; 52.3% (27,639) were female. Year 12 was the largest year group (21,274 (40.3%)). The proportion of pupils with special educational needs was higher for males (5,842 (23.2%)) than females (4,021 (14.6%) (p<0.001), although free school meals entitlement was similar (males 5,844 (23.2%); females 6,704 (24.3%)). Mean pupil attendance rate for 2018/2019 was 93.8% (SD:6.7%). There were 125 (65.5%) non-grammar and 66 (34.5%) grammar schools. Median Year 8-12 size was larger among grammar schools (675 pupils, Interquartile Range (IQR): 550,800) than non-grammar schools (median 500 pupils, IQR: 350,650). Among Year 12 students, 50.1% (5,891) of non-grammar school pupils obtained 5 or more GCSEs at grades A*-C (including English and Maths) compared to 93.5% of grammar school pupils. 73% (9,040) of A-level pupils proceeded to higher education. Conclusion The EOL 2018/2019 is the first wave of the Education Outcomes Linkage database for NI and will inform future planning policy in respect of post-primary education. Further studies are planned examining differences in educational attainment of pupils attending schools of different sizes accounting for characteristics of pupils and schools.